Purification Transformation to Progress in Salafi Thought Mas Mansur and His Contribution to Muhammadiyah - Gusman Sayyid Abdurrahman (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the transformation of purification towards progress in the Salafi thought of K.H. Mas Mansur and his contribution to the formation of Muhammadiyah's modernist character through the concepts of ijtihad, tajdid, and criticism of taqlid. Theoretical framework: This study uses an intellectual history approach, Islamic renewal movement theory, and a genealogical perspective to understand the relationship between the purification of faith, rationality, and social modernization in Muhammadiyah. Literature review: Previous studies generally position Muhammadiyah as a puritan or modernist movement in general, while the relationship between theological purification and the orientation of social progress in Mas Mansur's thought has not been studied comprehensively. Method: This study uses a qualitative method based on library research with a historical-genealogical approach and content analysis techniques on Mas Mansur's works, Muhammadiyah documents, and various academic literature related to modern Islamic renewal in Indonesia. Results: The study shows that purification in Mas Mansur's thinking is not only interpreted as a purification of faith from polytheism, bid'ah, and superstition, but also as a social transformation strategy to build rationality, work ethic, modern education, and awareness of the progress of the Muslim community. This thinking gave birth to a synthesis between the Salafi tradition, modern rationalism, and the social needs of society, which then formed the character of